Analisis Lokasi Warung Kopi (WARKOP) Literasi Terhadap Minat Pembelian Mahasiswa Untirta Sindangsari Banten - Vera Maria; Arifani Yanuar; M. Ikhwan Nur Rifki; Sofyan Ramadhan; Louissa Vedra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this research is to see how the Literacy Warkop location influences student buyer interest at Sultan Ageng Tirtayasa University (Untirta). Factors such as comfort, accessibility and atmosphere were studied through a survey conducted by twenty students. In this current era of globalization, a coffee shop is not only a place to enjoy coffee, but also a place to interact socially and intellectually. It is hoped that the location of the literacy shop near the library or academic building will increase student accessibility and comfort. The research results show that students' buying interest is greatly influenced by the right purchase location. The buyer's desire to buy something which is influenced by internal and external factors is called buying interest. This research helps business people determine location placement methods to attract student attention. Therefore, location maintenance is very important for the success of literacy warkop in attracting student customers.